Schoology-Based Learning Management Development On Badminton Courses - Indarto, Pungki; Jariono, Gatot; Nurhidayat, N; Ridlo, Maladhan Fajar; Hermawan, Iwan (CV. Inara, 2021)
Abstract.The purpose of this research is to develop learning management on Schoologybasedbadminton courses. The results are expected to know the validity,effectiveness, and response of students to the management of the learning. Theresearch was conducted in the FKIP UMS Sports Education Study Program. Thesubject of the study is a seventh-semester student in 2020. Research methods used byADDIE (Analysis, Design, Development, Implementation, Evaluation). The resultsshowed that the study of material experts obtained a score of 44 with a percentageof 81.43% with a very valid category. Media experts with a score of 85 with apercentage of 79% are included in the Valid criteria. Effectiveness of learningmanagement of 1.12 including Strong Effect. Students' responses to learningmanagement used scored an average of 80, 96%. This research concludes that thedevelopment of schoology-based learning management can be applied in badmintonlearning in universities.Keywords: management development, Schoology, badminton.